2022
DOI: 10.1021/acs.molpharmaceut.2c00663
|View full text |Cite
|
Sign up to set email alerts
|

Fn14-Directed DART Nanoparticles Selectively Target Neoplastic Cells in Preclinical Models of Triple-Negative Breast Cancer Brain Metastasis

Abstract: Triple-negative breast cancer (TNBC) patients with brain metastasis (BM) face dismal prognosis due to the limited therapeutic efficacy of the currently available treatment options. We previously demonstrated that paclitaxel-loaded PLGA−PEG nanoparticles (NPs) directed to the Fn14 receptor, termed "DARTs", are more efficacious than Abraxane�an FDA-approved paclitaxel nanoformulation�following intravenous delivery in a mouse model of TNBC BM. However, the precise basis for this difference was not investigated. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 89 publications
(176 reference statements)
1
12
0
Order By: Relevance
“…Furthermore, we have shown that paclitaxel-loaded, Fn14-targeted DART NPs exhibit significantly enhanced therapeutic efficacy compared to Abraxane, an FDA-approved paclitaxel nanoformulation, in murine models of primary TNBC and TNBC brain metastases . More recently, we have reported specific and significant targeting of Fn14-positive human and murine TNBC cells after systemic delivery into mice harboring intracranial tumors, further supporting the development of Fn14-directed nanotherapeutics for brain cancer treatment.…”
mentioning
confidence: 71%
See 1 more Smart Citation
“…Furthermore, we have shown that paclitaxel-loaded, Fn14-targeted DART NPs exhibit significantly enhanced therapeutic efficacy compared to Abraxane, an FDA-approved paclitaxel nanoformulation, in murine models of primary TNBC and TNBC brain metastases . More recently, we have reported specific and significant targeting of Fn14-positive human and murine TNBC cells after systemic delivery into mice harboring intracranial tumors, further supporting the development of Fn14-directed nanotherapeutics for brain cancer treatment.…”
mentioning
confidence: 71%
“…The latter condition was included for maximal PC formation. We used mouse serum in these studies to enable direct comparisons to our previous , and planned in vivo preclinical studies performed in mice. We quantified both the magnitude of NP cellular uptake (Figure A, B; Figure S5A) and the relative uptake of targeted NPs compared to control nontargeted NPs (Figure C, D; Figure S5B).…”
Section: Resultsmentioning
confidence: 99%
“…For example, recent preclinical models have demonstrated some efficacy in the use of paclitaxel-loaded polylactide-co-glycolide polyethylene glycol nanoparticles to target triple-negative breast cancer BM. 35 …”
Section: Discussionmentioning
confidence: 99%
“…Moreover, mice treated with the hybrid NP had more than a 50% increase in median survival compared to mice treated with the free form of the drugs. In a study conducted by Dancy et al, a PLGA‐PEG polymer NP was formulated with a targeting moiety against the cell surface receptor, fibroblast growth factor‐inducible 14 (Fn14), a tumor necrosis factor receptor that was shown to be overexpressed in different molecular subtypes of breast cancer, particularly TNBC 49,50 . Furthermore, besides Fn14‐selective targeting, these functionalized NPs possessed minimal nonspecific binding to brain extracellular matrix proteins 51 .…”
Section: Functionalized Nanoparticles To Enhance Drug Delivery To Bcbmmentioning
confidence: 99%
“…In a study conducted by Dancy et al, a PLGA-PEG polymer NP was formulated with a targeting moiety against the cell surface receptor, fibroblast growth factor-inducible 14 (Fn14), a tumor necrosis factor receptor that was shown to be overexpressed in different molecular subtypes of breast cancer, particularly TNBC. 49,50 Furthermore, besides Fn14-selective targeting, these functionalized NPs possessed minimal nonspecific binding to brain extracellular matrix proteins. 51 Thus, when loaded with paclitaxel, the so-called "decreased non-specific adhesivity, receptor tar- inhibited the adhesion, migration and invasion of murine 4T1 mammary carcinoma cells more effectively compared to unbound lapatinib.…”
Section: Functionalized Nanoparticles To Enhance Drug Delivery To Bcbmmentioning
confidence: 99%